Dr. Bronner's 'Magic Soaps' Religion: A Tikkun Olam Response to the Holocaust, the Atom Bomb, and the Cold War. - Chapman, Roger (Journal of Religion & Popular Culture)
This essay explores the historical and cultural context in which the late Emanuel Bronner began marketing Dr. Bronner's Magic Soaps, a natural brand known for its unusual labels that promote an 'All-One-God-Faith' solution for saving 'spaceship Earth.' An amalgamation of Judaism and American pluralism, Dr. Bronner's plan for world peace was a response to the anxieties caused by the Holocaust, the advent of atomic weaponry, and the ongoing Cold War. Although Dr. Bronner was an escapee from an insane asylum and came to be regarded as a kook, it should be recognized that he conformed to the behaviour of a prophet or holy fool. His message corresponds with tikkun olam, the Jewish vision of 'repairing the world.' Dr. Bronner's natural soaps and the accompanying call for global harmony served as a purification ritual for the American counterculture youth of the 1960s and 1970s.